Implementasi Peraturan Daerah Kabupaten Bungo Nomor 12 Tahun 2015 Tentang Penertiban Dan Pemeliharaan Ternak Di Kelurahan Manggis - Inayah, Dewi; Susanto, Joko; Chotib, M.; Anggraini, Zepa (Reformasi Administrasi, 2024)
This research is motivated by the fact that there are still many livestock roaming the public streets around the Manggis Village and disturbing the comfort of the community, so in order to realize the control of livestock, the Regional Government stipulates Bungo Regency Regional Regulation Number 12 of 2015 concerning Livestock Control and Maintenance. The purpose of this study is to determine the implementation and obstacles in the implementation of Bungo Regency Regional Regulation Number 12 of 2015 concerning The Control and Maintenance of Livestock. The method used is descriptive with a qualitative approach. The population in this study was all employees of Satpol PP Bungo Regency, Bathin III Subdistrict, Mangosteen Village and mangosteen village community. The analysis units studied were as many as 15 people who were determined by purposive sampling and accidental sampling techniques. The analysis used is an interactive model by Miles and Huberman. The results of this study indicate that the implementation of livestock control and maintenance in Bungo Regency Regional Regulation Number 12 of 2015 concerning Livestock Control and Maintenance in Manggis Village has not been carried out optimally because Satpol PP has not carried out activities for controlling livestock, transporting livestock, issuing summons to livestock owners and giving the results of the decision in the form of sanctions so that it does not give a deterrent effect to farmers. The obstacle in implementing the regional regulation is the lack of coordination between the sub-district and the Satpol PP so that enforcement has not been carried out in the Manggis Village. Lack of awareness of farmers in following existing regulations due to the habit of releasing livestock so that there are still many livestock roaming around.